Integrating spirituality into treatment : resources for practitioners - Miller, William R. (William Richard) (Washington, DC : American Psychological Association, 1999)
Provides clinicians with practical advice on including clients' spiritual perspectives in the therapeutic relationship. The book offers a history of the often tense relationship between spirituality and psychology and addresses broad, transtheoretical aspects of spirituality, including acceptance, forgiveness, hope, prayer, and meditation. It also introduces reliable and valid measures that can be used for assessing spirituality and provides examples of spiritually based interventions and collaborations that can enhance successful treatment. Finally, the book discusses professionals' responsibility to teach future therapists to embrace a range of spiritual perspectives and to demonstrate a sincere respect for client diversity. (PsycINFO Database Record (c) 2004 APA, all rights reserved)
Spirituality and treatment-- Addressing Spirituality in treatment-- Some spiritual issues in treatment-- Spirituality in professional training
[some parts are highlighted]
Includes bibliographical references and index.
Keywords: Psychotherapy -- Religious aspects; Spirituality